Preliminary results of a field tectonophysical study in the West coast of Antarctic Peninsula - A.V. Murovskaya; V.G. Bakhmutov (Ukrainian Antarctic Journal, 2015)
The purpose of the paper is to describe and analyze deformations of the mesolevel (joints, slickensides, folds and etc.) in the West Antarctica rock complexes of different age, to reconstruct the conformity stress fields and to identify deformation stages. We used the conventional structural geology techniques and methods of tectonophysics: structural- paragenetic (reconstruction of stress field by system of conjugated fractures) and kinematic (by slicken-sides). Totally 3246 joints, 23 slicken-sides, 126 dykes and 53 quartz veins were measured and other deformation structures were described at 105 observation points. For each observation point or group of points the stress tensor has been reconstructed, and for Argentine Islands areal distribution of the stress tensor orientations has been plotted. The regional stress field with horizontal NE-SW compressional axis and the horizontal NW-SE extensional axis has been identified. The orientation of the extensional axis across the strike of main rift structures allows us to relate their origination with extensional deformation stage. The conditions for extension of continental lithosphere could appear in the Early Cenozoic as a result of slab isolation during plate subduction. The compressional deformations are less and associated mainly with gabbros. The compressional stage preceded by extensional one and, probably, coincided in time with crystallization of gabbro massifs in Late Cretaceous. The anomalies in orientation of regional stress field have been revealed. They are associated with rotation of conjugate fracture in horizontal plane in the shear zones and can serve as their indicators. A lot of measurement on Galindez Island allowed to us reconstructed the local stress fields and the associated vertical movements. Inherited character of the fractures is revealed. It is shown that dikes and quartz veins use older system of discontinuities, whereas modem fractures are implemented on the existing dikes and contacts of various rock complexes.